Evaluating the flipped classroom: A randomized controlled trial. Issue 2 (3rd April 2018) - Wozny, Nathan; Balser, Cary; Ives, Drew
ABSTRACT: Despite recent interest in flipped classrooms, rigorous research evaluating their effectiveness is sparse. In this study, the authors implement a randomized controlled trial to evaluate the effect of a flipped classroom technique relative to a traditional lecture in an introductory undergraduate econometrics course. Random assignment enables the analysis to eliminate other potential explanations of performance differences between the flipped and traditional classrooms, while assignment of experimental condition by section and lesson enables improved statistical precision. The authors find that the flipped classroom increases scores on medium-term, high-stakes assessments by 0.16 standard deviation, with similar long-term effects for high-performing students. Estimated impacts are robust to alternative specifications accounting for possible spillover effects arising from the experimental design.